Makassar City Tourism Readiness in the New Normal Period of the COVID-19 Pandemic - Alamsyah, Andi Indra Saputra; Prasetya, Arik; Abdillah, Yusri (Journal of Indonesian Tourism and Development Studies, 2022)
Tourism plays a crucial role in driving economic growth, but the COVID-19 pandemic has severely affected the industry, including in Makassar City, Indonesia. This study aims to investigate the readiness of tourism to address the challenges posed by the pandemic and to identify the factors influencing this readiness. Specifically, the study focuses on the perceptions of tourism readiness based on the Travel and Tourism Competitiveness Index (TTCI) sub-index. Data was collected through surveys conducted in Makassar City using non-probability quota sampling. A quantitative-descriptive approach was employed, and the collected data were analyzed using multiple linear regression techniques. The study primarily examines the impact of two factors, namely the enabling environment and travel and tourism policy and enabling conditions, on tourism readiness. The study's findings reveal that enabling environment, travel, tourism policy, and enabling conditions contribute significantly to tourism readiness in Makassar City. However, the travel and tourism policy and enabling conditions variable influence tourism readiness substantially. Indicators such as the prioritization of travel and tourism indicators and the openness indicator received high scores, further supporting the significance of these factors. The implications of these findings are valuable for policymakers and government authorities involved in the tourism sector. The study provides valuable insights into the areas that need to be prioritized and improved to enhance tourism readiness in Makassar City. By focusing on creating an enabling environment and implementing effective travel and tourism policies, the government can shape strategies that foster resilience and recovery in the tourism industry amidst the ongoing challenges posed by the COVID-19 pandemic. Keywords: COVID-19 Pandemic, Economic Growth, Tourism Readiness, TTCI Sub-Index.